Implementasi Penegakan Hukum Promoter Dalam Penanggulangan Peredaran Gelap Dan Penyalahgunaan Narkotika Di Provinsi Lampung (Studi Pada Satuan Narkoba Sub Direktorat 3 Polda Lampung) - Chandra Wijaya (Universitas Widya Gama Malang, 2021)
Promoter is the concept of professionalism of the National Police, the main policy of the Promoter is the prevention of illicit traffic and narcotics abuse in Lampung Province. The research problem that will be discussed in this paper is how the efforts of the Lampung Police Narcotics Unit in overcoming illicit trafficking and drug abuse in the Lampung Regional Police jurisdiction and what are the inhibiting factors in overcoming illicit trafficking and drug abuse in the jurisdiction of Polda Lampung. Juridical normative and empirical research methods, using secondary and primary data, obtained from library research and field studies and data analysis with qualitative juridical analysis. Based on the results of research and discussion, it is known that the efforts of the Lampung Polda Narcotics Unit in overcoming illicit trafficking and drug abuse in the Lampung Regional Police jurisdiction are carried out in 3 (three) ways of pre-emptive, preventive and repressive efforts in overcoming illicit trafficking and drug abuse. Inhibiting factors including legal factors, law enforcement factors and the lack of informants are inhibiting factors because very few people are willing to be police informants. The suggestion that the writer can convey is that the Lampung Police Narcotics Unit should optimize guidance to the community in efforts to combat illicit traffic and drug abuse and it is hoped that the Lampung Police Narcotics Unit will improve coordination between elements of the criminal justice system, so as to provide positive synergy in efforts to combat illicit trafficking and abuse. drugs in the jurisdiction of the Lampung Regional Police will be achieved very well.